Usability and Software Architecture: A Literature Review - Vilela, Jéssyka; Figueiredo, Bruno; Castro, Jaelson; Soares, Monique; Gonçalves, Enyo (Anais do Simpósio Brasileiro de Componentes, Arquiteturas e Reutilização de Software (SBCARS); 2015: Anais do IX Simpósio Brasileiro de Componentes, Arquiteturas e Reutilização de Software, 2015)
In the literature, there are available proposals that aim to contribute to bridge the gap between user interface designers and software engineers. These proposals attempt to produce architectural solutions that successfully address the usability requirements. The objective of this paper is report the planning, execution and the results of a systematic review regarding the works about usability and software architecture. We investigated the definitions, the relationship between these two areas, the impact, problems, methods, tools, reports of success or failure, and finally, the contributions of existing solutions to the academy and the industry. From the 22 selected studies, it was possible to confirm that usability has an impact on software architecture. The methods used to bridge the gap between these areas use mainly patterns, scenarios, and usability evaluation of the architecture. Furthermore, it is possible to conclude that the proposed methods and tools require more empirical evidence.